2007
DOI: 10.1002/ijc.23146
|View full text |Cite
|
Sign up to set email alerts
|

HCCRBP‐1 directly interacting with HCCR‐1 induces tumorigenesis through P53 stabilization

Abstract: Oncogene HCCR-1 functions as a negative regulator of the p53 and contributes to tumorigenesis of various human tissues. HCCR transgenic mice developed breast cancers but it is unknown how HCCR-1 contributes to human tumorigenesis. This study identified a HCCR-1-binding protein 1 (HCCRBP-1) as an HCCR binding partner by performing yeast two hybrid screening. Their endogenous interaction was further confirmed by coimmunoprecipitation experiments. These two proteins colocalized in the mitochondria. HCCRBP-1 was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In addition, the p53 protein is well known as the master regulator of the p21 gene (22,23). In agreement with previous reports demonstrating the function of HCCR2 as a negative regulator of p53 in tumorigenesis (8,13,14), we found that HCCR2 was overexpressed and accompanied with an almost null expression of p53 in K562 cells. Furthermore, p53 expression was markedly upregulated following transfection with HCCR2-siRNA, which was consistent with the increased number of apoptotic K562 cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the p53 protein is well known as the master regulator of the p21 gene (22,23). In agreement with previous reports demonstrating the function of HCCR2 as a negative regulator of p53 in tumorigenesis (8,13,14), we found that HCCR2 was overexpressed and accompanied with an almost null expression of p53 in K562 cells. Furthermore, p53 expression was markedly upregulated following transfection with HCCR2-siRNA, which was consistent with the increased number of apoptotic K562 cells.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that HCCR2 is not only overexpressed in human cervical cancer tissues, but is expressed at high levels in a variety of human malignancies, including breast, kidney, stomach, colon, liver and ovarian cancer (8)(9)(10)(11)(12)(13). The functional role of HCCR2 in tumorigenesis may involve the negative regulation of the p53 tumor suppressor gene (8,13,14). Animal experiments have demonstrated that HCCR2-transgenic nude mice form spontaneous breast tumors, which further confirms the crucial role of HCCR2 in tumorigenesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…terized as a mitochondrial protein (26). We verified its subcellular localization when heterologously expressed in yeast.…”
Section: Synthetic Growth Effect Of Triple Disruptions Of Mdm38 Mrs7mentioning
confidence: 94%
“…6A). The recent work of Kim and co-workers (9,26) showed that HCCR-1 was overexpressed in various human cancers and might function as a negative regulator of the p53 tumor suppressor. Having shown that overexpression of LETM1 from the ADH promoter restored growth of the triple mutant, we tested the suppression capacity of HCCR-1 expressed under the same promoter.…”
Section: Synthetic Growth Effect Of Triple Disruptions Of Mdm38 Mrs7mentioning
confidence: 99%
“…16,17 Accumulated data demonstrate that HCCR was not only over-expressed in human cervical cancer tissues but also found to have high-level expression in various human malignancies including breast, kidney, stomach, colon, liver, and ovarian cancer. [15][16][17][18][19][20][21] The functional role of HCCR in tumorigenesis may be related to the negative regulation of the p53 tumor suppressor gene. 16,21 HCCR1-or HCCR2-transgenic nude mice could form spontaneous breast cancers, which further confirmed the critical role of HCCR in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%